Corporate Governance and Capital Structure on Firm Value with Dividend Policy Moderation - Putri Maurilla Afifah; Omi Pramiana (Proceeding International Conference on Digital Education and Social Science, 2025)
This research examines how Good Corporate Governance (GCG) and capital structure affect company valuation, with dividend policy serving as a moderator, among LQ45 firms on the Indonesia Stock Exchange from 2022 to 2024. Employing a quantitative method, it utilizes secondary data from annual reports, encompassing 29 companies and 87 data points. Company value is gauged via Price to Book Value (PBV), while other factors rely on governance metrics and financial ratios. Findings indicate that GCG boosts company value, but capital structure harms it due to rising leverage risks. Dividend policy reinforces this dynamic and acts as a favorable cue to investors. These insights underscore the value of strong governance, careful capital management, and reliable dividend strategies in enhancing LQ45 firm valuations.